A preliminary investigation: children’s awareness of child sexual abuse in Malaysia - Othman, Azliza (International Association of Computer Science and Information Technology Press (IACSIT Press), 2013)
This paper reports the feedback from respondents in relation to the implementation of Persuasive Multimedia Learning Awareness in preventing child sexual abuse in Malaysia.A qualitative method using unstructured interview has been selected as a technique of gathering information in order to identify the current children awareness toward sexual abuse and current child sexual abuse prevention programs implemented in Malaysia. Four respondents have been selected to participate in this interview: a representative from the Department of Social Welfare, government agency involved in making Child Protection Policy; a representative from Women’s Centre for Change (WCC), Penang, an NGO involved in prevention program, a representative from Family Law Division, Department of Islamic Affairs, State of Kedah (JAIK) and a primary school teacher. The findings from this preliminary investigation confirm that in Malaysia, there is a need to educate children about child sexual abuse and there is still lacking of educational materials that utilize multimedia and computer technology that teach children about personal safety. In conclusion, the implementation of Persuasive Multimedia Learning need to be designed and developed to educate children and to increase their awareness level of any situations that might negatively affect their personal safety and to provide guidelines for the children on how to act appropriately when these situations arise.